KEBIJAKAN AKREDITASI SEKOLAH DAN MADRASAH - Afriansyah, Muhammad; Abdullah Idi; Febriyanti; Ahmad Zainuri (STKIP Subang, 2026)
This study aims to analyze school and madrasah accreditation policies in Indonesia as an instrument for ensuring educational quality and to identify supporting and inhibiting factors in their implementation. Accreditation is a form of external evaluation conducted by the National Accreditation Board for Schools/Madrasahs (BAN-S/M) with reference to the National Education Standards (SNP). This study uses a qualitative approach with library research methods through analysis of regulations, scientific literature, and related policy documents. The results show that accreditation policies play a strategic role in improving educational quality through standardization, accountability, and transparency. The use of digital systems such as Sispena S/M also increases the efficiency and objectivity of the accreditation process. Supporting factors include commitment to quality improvement, national standardization, and encouragement of innovation in educational institutions, while inhibiting factors include limited human resources, administrative readiness, and facilities and infrastructure. Therefore, effective and sustainable accreditation management is needed to optimally improve educational quality.